Computational study of early-time droplet impact dynamics on textured and lubricant-infused surfaces. (April 2023) - Henman, Nathaniel I.J.; Smith, Frank T.; Tiwari, Manish K.
Abstract: The high-speed impact of liquid droplets onto surfaces with different properties is a vast area of research. The present study focuses on using numerical simulation to investigate the delicate early stages of droplet impact onto both textured and lubricant-infused surfaces. An idealised two-dimensional model is utilised for a normal impact of an incompressible liquid droplet onto a surface of rectangular asperities and a thin layer of lubricant. In experiments the length scale of the impinging droplet is typically much larger than that of the surface asperities. The study here aims to complement such work by considering the same scaling, with millimetre sized droplets impinging on surfaces with micrometre sized asperities. It is found that variations of the surface properties have an insignificant effect on the location of the jet root and all dynamical changes are focused in the thin splash jet ejected at impact. The effects that the parameters pertaining to a lubricant-infused surface, namely the surface topology, lubricant depth and lubricant viscosity, have on the extent of the thin splash jet are investigated in turn. Increasing the gap between the surface asperities results in a reduction in the horizontal extent of the splash jet, while variations in lubricant depth and viscosity exhibit non-monotonic effects. In each case phase diagrams are presented to characterise the early time splashing behaviour and investigate the influence of impact velocity. Comparisons of a lubricant-infused surface to a superhydrophobic surface, with no lubricant present, highlight the importance of the surface topology. The results presented in this manuscript also highlight possible avenues of further research, both analytical and experimental, as well as aid in the design of novel non-wetting surfaces. Highlights: Increasing distance between pores on LIS can reduce splashing. Depth and viscosity of lubricant exhibit non-monotonic effects on splashing. For small pore sizes, more splashing seen on LIS compared to textures surfaces. For moderate pore sizes, more splashing seen on textured surfaces compared to LIS.